O ensino de Química nas escolas públicas da Diretoria de Ensino de Votorantim (SP): um estudo de caso - Mariussi, Mariana Penna (2015)
The research aims to investigate the Chemistry teacher profile who works in state public schools in the Department of Education of Votorantim (SP). For that, it is intended to analyze the teacher‟s group profile who teach Chemistry in those schools, considering aspects such as graduation (specific and pedagogical education), how those workers see the teaching and the learning process of Chemistry, the difficult points they find in their career and to characterize the teachers‟ continuing education. It is believed that several difficulties related to the teaching and learning process of Chemistry in the Elementary Education can be related to the initial training program of the Chemistry teachers, mainly by the fact that in many universities the curriculum framework of teaching is linked to the bachelor education, restraining the specific Chemistry contents to be transformed in the pedagogical ones so that the pedagogical education composes the practical education of the teacher, being a initial education based on the technical rationality model. For an effective research, the qualitative methodological approach was opted, with a study case, where it will be investigated the professional profile of a group of teachers, their conceptions about education and the teaching strategies they use to promote the learning process of their students. For the data collection two instruments were used: a questions report and a semistructured interview. The questions reports were applied during a Technical Chemistry Orientation (held in the Pedagogical Workshop Place of the Department of Education in Votorantim), to meet a large number of Chemistry teachers. Questions were based on structured data which allowed the creation of a profile of those professionals, answering the main question who are these teachers . Just the graduate teachers in Chemistry who accepted to join the interview were heard. The interviews permitted the analysis on how the pedagogical and specific education of those workers was established and how to characterize their continuing education. Besides, they also permitted the comprehension on how those professionals see the teaching and learning process of Chemistry among the students and the difficulties they face in their teaching practice.